TRiFLe, a Program for In Silico Terminal Restriction Fragment Length Polymorphism Analysis with User-Defined Sequence Sets - Junier, Pilar; Junier, Thomas; Witzel, Karl-Paul (My University, 2008)
We describe TRiFLe, a freely accessible computer program that generates theoretical terminal restriction fragments (T-RFs) from any user-supplied sequence set tailored to a particular group of organisms, sequences from clone libraries, or sequences from specific genes. The program allows a rapid identification of the most polymorphic enzymes, creates a collection of T-RFs for the data set, and can potentially identify specific T-RFs in T-RF length polymorphism (T-RFLP) patterns by comparing theoretical and experimental results. TRiFLE was used for analyzing T-RFLP data generated for the amoA and pmoA genes. The peaks identified in the T-RFLP patterns show an overlap of ammonia- and methane-oxidizing bacteria in the metalimnion of a subtropical lake.